Chemical synthesis of tripeptide thioesters for the biotechnological incorporation into the myxobacterial secondary metabolite argyrin via mutasynthesis - Siebert, David C. B.; Sommer, Roman; Pogorevc, Domen; Hoffmann, Michael; Wenzel, Silke C.; Müller, Rolf; Titz, Alexander (Beilstein Journal of Organic Chemistry, 2019)
The argyrins are secondary metabolites from myxobacteria with antibiotic activity against Pseudomonas aeruginosa. Studying their structure–activity relationship is hampered by the complexity of the chemical total synthesis. Mutasynthesis is a promising approach where simpler and fully synthetic intermediates of the natural product’s biosynthesis can be biotechnologically incorporated. Here, we report the synthesis of a series of tripeptide thioesters as mutasynthons containing the native sequence with a dehydroalanine (Dha) Michael acceptor attached to a sarcosine (Sar) and derivatives. Chemical synthesis of the native sequence ᴅ-Ala-Dha-Sar thioester required revision of the sequential peptide synthesis into a convergent strategy where the thioester with sarcosine was formed before coupling to the Dha-containing dipeptide.
Keywords: antibiotic; argyrin; mutasynthesis; NRPS; peptide synthesis